MENINGKATKAN KETERAMPILAN BERBICARA TEKS ANEKDOT MELALUI MODEL PEMBELAJARAN ROLE PLAYING BERBASIS KONSTRUKTIVISME PADA PESERTA DIDIK KELAS X IPA-1 MAN SIDOARJO - Winawati; Tri Indrayanti (Universitas PGRI Adi Buana Surabaya, 2019)
This research aim to improve speaking skills by using role playing learning models based on constructivism in the tenth grade science-1 students of MAN Sidoarjo. The type of this research use collaborative action research. The theory used in this research is the theory of speaking skills from Arsjad and Mukti. The technique of analyzing data used quantitative and qualitative descriptive. The results showed that role playing learning models based on constructivism can improve students speaking skills by the teachers deliver the learning objectives, explain the role playing activities, divide the students into small groups, motivating the students to understand the material, give the students facilities to play a role, and guiding the students to discuss evaluate the role playing activities. The results showed that the learning process is increased. The improvement can be seen from the enthusiasm of the students and the students more orderly during the learning activities. Speaking skills improvement showed from the average acquisition value, before using the method increased about 49,34% to 75,68% in the first cycle and increased to 80,90% in the second cycle.